Meningkatkan Keterampilan Menulis Artikel Ilmiah Melalui Pelatihan Penulisan Publikasi bagi Mahasiswa Pendidikan Antropologi Fakultas Ilmu Sosial Universitas Negeri Makassar - Darmayanti, Dyan Paramitha; Arifin, Iqbal; Syarif, Kurnia Ali; Seppa, Yusi Irensi; Asmunandar, Asmunandar (Universitas Negeri Makassar, 2024)
The purpose of this community service is to increase the knowledge and understanding of Anthropology Education Study Program students of the Faculty of Social Sciences and Law about scientific article writing training. It is hoped that this PKM will help students of the Anthropology Education Study Program, Faculty of Social Sciences and Law in writing scientific articles. The service activity consists of three stages. The first is preparation, which includes preparing training materials and materials, field observations, and determining the training location. The second stage is the preparation of proposals and research implementation. The third stage is writing scientific articles. Participants must be able to compile scientific articles properly and precisely, which shows that this activity is successful.